A combined review of vibration control strategies for high-speed trains and railway infrastructures: Challenges and solutions. Issue 1 (March 2023) - Zhang, Chunwei; Kordestani, Hadi; Shadabfar, Mahdi
People use trains as a means of transportation to travel to various nearby and distant destinations, resulting in an increasing amount of time spent inside such vehicles. Consequently, railway transportation sectors are focusing significantly more on enhancing passengers' demand and level of satisfaction, including but not limited to high-speed travel, safety, and riding comfort. This paper provides a state-of-the-art review of available solutions for reducing undesired vibrations that have a substantial impact on improving the critical velocity limits of trains, maintaining the quality of riding comfort, and resolving safety concerns. In this regard, the solutions proposed for train vibration control are divided into two main categories: direct and indirect solutions. The direct solutions are those methods that are applied directly to trains' bodies or bogies to attenuate the undesired vibrations, for example, improving the suspension/damper system, implementing active/semi-active control strategies, or applying various carriage optimization design modifications. Indirect solutions, on the other hand, are those that could indirectly affect trains' vibrations, for example, controlling vibrations in railway bridge structures during train passages. Since the identification of vibration characteristics is assumed to be the first step in choosing proper solutions, particularly for active or semi-active control implementations, this review has examined the literature pertinent to modal identification of trains and railway infrastructures. Additionally, despite the installation of dampers between the bogie and suspension, the train's equation of motion, and consequently, the vibration control of the bogie, has relied on the sky-hook model for decades. The fundamental problem for systems whose control strategies are based on the sky-hook concept is that the 'sky' does not actually exist. A solution to solve the sky-hook logic issue is using tuned rotatory inertia dampers and active rotatory inertia drivers which is addressed in this paper as well. Finally, it is concluded that these three solutions – employing a suspension/damper system in the bogie, an elastic connection for the train's under-chassis-suspended equipment, and a ballastless railway – can practically mitigate vibration and noise in a train.